Incidencia del COVID-19 en el rendimiento deportivo de velocistas juveniles de 100 y 200 metros - del Carmen Jaramillo Ogonaga, L. M. (Lecturas: Educación Física y Deportes, 2021)
Introduction: Faced with the COVID-19 pandemic, the sports training processes that have had to adapt to the new conditions imposed by the health system. Knowing specifically these implications makes it possible to improve decision-making, at the same time that it will allow to define what effects the new training strategies have had when maintaining and increasing sports performance. Objective: To compare the results of nine tests before and after the start of the COVID-19 pandemic in 100 and 200 meter youth sprinters. Methods: Descriptive-explanatory research of a correlational order, comparing results in nine tests carried out before and after the COVID-19 pandemic began in 22 youth sprinters. Results: All means were lower in terms of performance in post-test, in Long Jump (Pretest: 2.25m and Posttest: 2.11m; -14cm), Right and Left Leg (Pretest: 11.20m and Posttest: 11.14m; -0.06cm; Pretest : 11.09m and Posttest: 11.04m; -0.5cm), in 40m and 60m (Pretest: 5.62 seconds and Posttest: 5.62 seconds; Pretest: 8.05 seconds and Posttest: 8.16 seconds; +11ms respectively), in 1000m (Pretest: 3.95 minutes and Posttest: 4.03 minutes; +0.8 minutes), in Abs (Pretest: 46 movements and Posttest: 43 movements; -3 movements), in Dorsal (Pretest: 117 movements and Posttest: 115 movements; -2 movements), and in Arm flexibility (Post-test: 37° and Post-test: 41°; +4°), although there were no significant differences in any of cases. Conclusions: There is evidence of a decrease in specific performance in the studied indicators, showing that the alternative training strategies were not optimal, with the real decrease possibility in personal records.